Comparative Study of Cosmonims (Sun, Moon ...) In Uzbek and English - Usmonova Shaxnoza (Genius Journals, 2022)
The concept of cosmonims is related to terms related to the field of cosmonautics. The naming of objects as unique or common in space stems from the fact that each language has its own lexicography. In this article, the author discusses the differences and similarities of cosmonims in Uzbek and English.
Keywords: Cosmonims; Sun; Moon; lexicography